Effect of the 10% nitric acid and 10% chromic acid ratio on the quality of maceration preparations - Ariella Junes Egalita; Farida Indirahma; Auberta Myra Ardelia; Dhiga Agung Sasongkojati; Aliffian Nisa Cholida; Sri Wahyuni (Green and Tropical Laboratory for Sustainability, 2025)
Background: Maceration is a microtechnique used to examine xylem vessel anatomy by softening plant tissues in specific solutions so that tracheary elements can be observed clearly. However, the optimal ratio of acid solutions for producing durable and well-stained maceration slides is still rarely reported for Piper betle. Objectives: This study compared two ratios (1:1 and 1:5) of 10% nitric acid and 10% chromic acid to evaluate their effects on the quality of maceration preparations from green betel (Piper betle) stems. Methods: An experimental design was applied. Stem and petiole samples were processed through boiling, acid soaking, staining with safranin and methylene blue, graded alcohol dehydration, and fixation/clearing using xylol. Observations were conducted under 400× magnification, and findings were summarized descriptively Results: The 1:1 ratio produced more uniform staining and more resilient preparations than the 1:5 ratio. Slides prepared with the 1:5 ratio tended to be more fragile and exhibited less optimal staining, likely due to excessive chromic acid. Methylene blue staining was weak in both treatments, consistent with the dye’s high water solubility and possible incomplete rinsing after acid treatment. Conclusion: Maceration was effective for observing xylem anatomical structures in P. betle. A 1:1 ratio of 10% nitric acid to 10% chromic acid is recommended to obtain better slide quality and durability for microscopic observation.